Hydrocarbon charging processes of deep fractured-vuggy dolomite reservoirs in the Ediacaran Dengying Formation, Southern Sichuan Basin, SW China - Jin, Hongxiang (Frontiers in Earth Science, 2025)
The largest carbonate gas field in China has been discovered in the Cambrian-Ediacaran of Central Sichuan Basin. Despite the enormous resource potential, differences in hydrocarbon-charging conditions have limited subsequent exploration and development in Southern Sichuan Basin. Based on biomarker compounds, hydrocarbon generation history, homogenization temperature of fluid-inclusions, carbon isotopes and other data, the key scientific issues faced in the restoration of hydrocarbon-charging processes were analyzed, and the evolution models of Ediacaran petroleum system in different areas were established. The results show that: (1) The quality of the Cambrian Maidiping source rocks is better than the Qiongzhusi Formation, and its kerogen type is Type I. The maturity of the Maidiping source rocks is high and in the stage of over-matured evolution. (2) Dengying natural gas is a mixed product of oil-cracking gas and kerogen-cracking gas, and the sources and origin vary greatly in different areas and wells. Natural gas in the WY Gas Field comes from the Qiongzhusi source rocks, while the proportion of Maidingdi source rocks for gas supply in the fourth Member of the AY Gas Field and second Member of the Ziyang area is significantly higher. As the main source rock, the Qiongzhusi Formation entered the hydrocarbon-generation process from the late Silurian and began to uplift and end hydrocarbon-generation in the late Cretaceous. The Permian and Triassic are the main oil-generation periods. The gas-generation period lasted from the Late Permian to the end of the Early Cretaceous, with the Jurassic being its main gas-generation period. The hydrocarbon-charging processes of the Ediacaran petroleum system in Southern Sichuan went through three stages: the formation stage of paleo-oil reservoirs in the Caledonian-Hercynian period, the cracking stage of oil into gas in the Indosinian-Yanshanian period, and the adjustment and finalization stage of gas reservoirs in the Himalayan period.